2022
DOI: 10.1029/2022sw003042
|View full text |Cite
|
Sign up to set email alerts
|

Solar Tide‐like Signatures in the Ionospheric Total Electron Content During the 2018 Sudden Stratospheric Warming Event

Abstract: Atmospheric waves play an important role in the vertical coupling of atmosphere and ionosphere. Recent studies revealed that the mesospheric wave activities associated with sudden stratospheric warming events (SSWs) are more complicated than previously thought. This study investigates the activities of the dominant solar tide‐like harmonics in the ionosphere during SSWs. Significant tide‐like harmonics are present in the residuals of total electron content (TEC) detected by five receivers at different latitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Taking into consideration that the three meteor radars are located at similar longitudes with the four selected ionospheric stations (in Juliusruh station a meteor radar and a ionosonde radar coexist) and the fact that the onset of the selected SSW events occurred towards the end of January or beginning of February, we believe that the short tidal periodicities of ionospheric layers detected over Moscow (and over the 3 high midlatitude European ionosonde stations in our previous study) primarily during December and January may be attributed to the enhancement of the higher-order atmospheric tides prior to the SSW events. In support to this conclusion, Ma et al (2022) showed that tidal waves with the same periodicities (mainly 12, 8 and 6-h) may also appear in Total Electron Content(TEC) and they can exhibit a similar response to a SSW event (weaken after SSW onset). They actually reported a TEC response, consistent with He et al (2020) results after the SSW onset in the year 2018.…”
Section: Shorter-scale (4-and 48-hour) Periodicities In Idl and Es Oc...mentioning
confidence: 79%
“…Taking into consideration that the three meteor radars are located at similar longitudes with the four selected ionospheric stations (in Juliusruh station a meteor radar and a ionosonde radar coexist) and the fact that the onset of the selected SSW events occurred towards the end of January or beginning of February, we believe that the short tidal periodicities of ionospheric layers detected over Moscow (and over the 3 high midlatitude European ionosonde stations in our previous study) primarily during December and January may be attributed to the enhancement of the higher-order atmospheric tides prior to the SSW events. In support to this conclusion, Ma et al (2022) showed that tidal waves with the same periodicities (mainly 12, 8 and 6-h) may also appear in Total Electron Content(TEC) and they can exhibit a similar response to a SSW event (weaken after SSW onset). They actually reported a TEC response, consistent with He et al (2020) results after the SSW onset in the year 2018.…”
Section: Shorter-scale (4-and 48-hour) Periodicities In Idl and Es Oc...mentioning
confidence: 79%
“…Since the modeling results only describe the climatological behaviors, the short‐term differences in the amplitudes and phases between the CODE derivations and reconstructions could be associated with the geomagnetic activities and lower atmosphere disturbances. In recent years, the activities in the lower atmosphere were found to play a considerable role in the day‐to‐day variations in the ionosphere, especially during the sudden stratospheric warming period (Baldwin et al., 2021; Ma et al., 2022). However, this climatic modeling would serve as a reference for further investigation of the ionosphere changes under disturbed space weather conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A good specification of these tide‐like signatures is expected to rebuild the diurnal variabilities in the ionosphere. Previous works usually concentrate on the amplitudes of the tide‐like perturbations, for example, the mean behavior or its response to the space weather disturbance, but limited attention was paid to the phase changing (Baldwin et al., 2021; Ma et al., 2022). Furthermore, a good parameterization of the seasonal and interannual variations in the tidal phase could also shed light on further investigations of the mechanism and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…H. Ma et al. (2022) studied the solar tide‐like harmonics from 12 to 6 hr in TEC detected by fixed ionospheric piercing points of Beidou Geostationary Orbit (BD‐GEO) C3 satellite during the 2018 SSW. These works can only gain the period information of the tide but not the wave number.…”
Section: Introductionmentioning
confidence: 99%
“…Although they have same periods and even wave numbers as tides in the neutral winds. They may be wave structures which are excited locally or modulated by magnetic fields (H. Ma et al., 2022). Therefore, the expressions “tide‐like signatures/components” are used for representing the tidal signatures/components in the ionosphere for this work.…”
Section: Introductionmentioning
confidence: 99%